1986
DOI: 10.1104/pp.81.3.742
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Transport and Compartmentation in Spergularia marina

Abstract: ABSTRACrIn this paper, a combination of tracer uptake, efflux, and pulse-chase techniques is applied to the problem of compartmentation of Na ' (4Nal) in the roots of intact, midvegetative Spergularia marina (L.) Griseb. plants. An approach is presented for conducting useful compartmental analysis when it is known that the assumptions required for staightforward interpretations of influx and efflux studies are invalid. Linear rates of 2'Na' accumulation in both roots and shoots were attained within at mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 22 publications
4
25
1
Order By: Relevance
“…Lazof and Cheeseman (1986) suggested that a small and labile symplastic pool that was involved in the upward transport of Na+. Based on the fact that membrane-impermeable tracers, such as La3+ ), raffinose (Perry and Greenway 1973), and PTS (Hanson et al 1985;Moon et al 1986;Yeo et al 1987), could be detected in the shoots or xylem exudate when the tracers were applied to intact roots, the occurrence of long-distance transport which bypasses membranes had been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Lazof and Cheeseman (1986) suggested that a small and labile symplastic pool that was involved in the upward transport of Na+. Based on the fact that membrane-impermeable tracers, such as La3+ ), raffinose (Perry and Greenway 1973), and PTS (Hanson et al 1985;Moon et al 1986;Yeo et al 1987), could be detected in the shoots or xylem exudate when the tracers were applied to intact roots, the occurrence of long-distance transport which bypasses membranes had been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The second factor is the efficiency of the rinsing procedure in removing apoplastic "5N with minimal loss of symplastic "5N. Similar rinsing procedures have previously been shown to effectively remove cationic radiotracers from the free space without significant loss of label from membrane-bound pools (10). Loss of internal NO3-was tested in preliminary studies, exposing intact seedlings to 0.1 mM [5N]NO3-for 3 d, rinsing roots in 8 mm CaSO4 at 0°C for 2 min to remove free space NO3-, and then rinsing in a large volume of 8 mm CaSO4 at 0°C (5 I/plant) for 30 min.…”
Section: Localization Of Nitrate Absorption and Translocationmentioning
confidence: 99%
“…Results from short-term time courses of uptake by intact roots indicate that symplastic ion transport across the root to the xylem can occur within a few minutes (e.g. 10,12,15,21), so that considerable interregional transport is likely to occur with exposure to labeled nutrients for 30 min or more.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This exacerbates the energy problem; it is not simply a problem at the plasmamembrane. Clearly, there is still something critical we are missing about the status of Na + in cells (Lazof and Cheeseman 1986). …”
Section: Transportersmentioning
confidence: 99%